270 A phase II basket trial of dual anti-CTLA-4 and anti-PD-1 blockade in rare tumors (DART) SWOG S1609: the thyroid tumor cohort. (9th November 2020) - Chae, Young Kwang; Othus, Megan; Patel, Sandip; Fenton, Sarah; Wang, Ding; Rodriguez, Cristina; Onitilo, Adedayo; Mattour, Ahmad; Rybkin, Igor; Hayward, Jourdain; McLeod, Christine; Chen, Helen; et al.
Abstract : Background: Checkpoint inhibitors acting against PD-1 and CTLA-4 have provided significant benefit for patients. However, their efficacy in rare tumors has not been determined. This abstract presents the results of combination therapy with anti-CTLA and anti-PD-1 in the thyroid cohort of SWOG S1609 Dual Anti-CTLA-4 & Anti-PD-1 blockade in Rare Tumors (DART). Methods: This study is a prospective, open-label, multicenter phase 2 clinical trial of ipilimumab (1 mg/kg intravenously every 6 weeks) plus nivolumab (240 mg intravenously every 2 weeks) in rare tumors. Here we report the outcomes from thyroid cancer patients. The primary endpoint is objective response rate (ORR) (RECIST v1.1) (confirmed complete response (CR) and partial responses (PR)); progression-free survival (PFS), overall survival (OS), stable disease (SD) >6 months, and toxicity are secondary endpoints. Results: Twenty-one patients were registered and seventeen were eligible and received therapy. Median age of the patients was 59 (range 33–78), 59% (N=10) of enrolled patients were male. The most common subtype of thyroid cancer was papillary (47%, N=8), then medullary (24%, N=4), anaplastic (24%, N=4) and Hurtle cell histology (6%, N=1). The ORR was 12% [CR, 0%, N= 0; PR, 12%, N= 2; 1 papillary and 1 anaplastic subtype]; in addition 12% (N=2) had unconfirmed PR (both papillary subtype). Of note, 1 out of 4 patients with anaplastic thyroid carcinoma (25%) had a response that lasted more than two years. 35% (N=6) of patients had SD for over 6 months, 12% (N=2) had SD for less than 6 months (figure 1 a&b). Clinical benefit rate including all PRs and SD over 6 months was 59% (N=10/17). Additionally, one patient with papillary thyroid carcinoma that withdrew early due to toxicities (neuropathic pain and arthralgias) had stable disease for over one year (not included in response assessment). 6-month PFS was 58% (95% confidence interval; 39–88) and median PFS was 9.5 months (4.99-infinity); 6-month OS was 88% (74–100%) and median OS was not reached. One patient died while enrolled. 94.1% (N=16) experienced toxicities with 52.9% (N=9) experiencing grade 3–5 toxicities. The most common adverse events were fatigue (41.2%, N=7), elevated lipase (29.4%, N=5), acute kidney injury, diarrhea, muscle weakness, anorexia, pruritis, nausea and alanine aminotransferase elevation (21.1%, N=3 each). The most common immune-mediated adverse events were acute kidney injury and elevated lipase (29.4%, N=5 each). Conclusions: Combination therapy with ipilimumab plus nivolumab in thyroid cancer resulted in an ORR of 12% with two partial responses in seventeen treated patients. Trial Registration: NCT02834013 Ethics Approval: The study was approved by the NCI Adult Central Institutional Review Board, approval number 02834013.